“Think of It No Longer as a Broken Yew-Tree…but as a Living Witness”: The Cultural and Ecological Meaning of Iconic Trees - Helen Parish (Histories, 2025)
Across the centuries, trees have been recognised as one of the oldest lifeforms on earth, witnessing and subject to the passage of time on a scale that far exceeds human life, telling us who we are in the world. This paper explores the intricate nature of human interactions with trees across a broad chronological and conceptual range, and the cultural, symbolic, and ecological meaning of “iconic” trees, drawing upon a selection of case studies to explore and analyse the relationship between the tree as a living organism and its cultural, textual, and mnemonic meaning. In conducting this, it reflects upon the cultural geographies of presence and absence, and the role of emblematic trees as places of memory and structures of belief. The relationship between human life and the life of trees is shown to be symbiotic; multiple cultural values and symbolic forms are ascribed to trees, and those same trees shape the physical, ecological, and human environment. The social and cultural construction of the landscape and sites of memory is presented as a key component in the formation of narratives and mentalities that define the relationship between humans and iconic trees, material and imagined. Physical, ecological, and cultural erosion, it is suggested, have the capacity of memorialising forgetfulness and creating a space in which the absence of presence and the presence of absence co-exist. The iconic image of the fallen tree, in its presence and absence, exposes the extent to which trees are also human objects, constructed and understood in human terms, and subject to a range of personal, political, and pragmatic impulses. A tree can be iconic not simply because of what it was but because of what it was believed to be, integrating a physical, historical, memory, and ecological or cultural space into our relationship with the natural world.